«Били смертнимъ боεмъ, и на вербѣ вішали стрεмглавъ, и вεлѣли щεкати аки псу по подъ ихъ ногами»: документи судової справи козака Федора Проскурненка (Частина друга) - Синяк, І. (Сiверянський літопис, 2021)
The purpose of the publication is to introduce into scientific circulation documents that cover the claim and the course of the court case of the cossack Fedor Proskurnenko (Proskurnya) from Pokoshichi of the Ponornytsia squadron of the Chernihiv regiment against fellow villagers Karp Vlasenko and Pylyp Fedosenko for illegally appropriated honey trees and for bullying and humiliation. The research methodology is based on general scientific methods of analysis and synthesis. L. Z. Gistsova’s “Methodical recommendations on preparation for the publication of the Kosh Archive of the New Zaporozhian Sich” was used in the preparation of documents for printing. The scientific novelty is that for the first time the documents of the mentioned court case, which are stored in the Narodowa Library (Poland, Warsaw), were introduced into scientific circulation, their informative potential was analyzed and commented on. Conclusions. The published documents significantly expand the understanding of the judiciary of the Ukrainian state of the first third of the XVIII century, social communications, court records and document management, enrich the biography of the government officer of the Chernihiv regiment, and revenge information about the historical toponymy of the region.